Complete genome sequence of the orange-red pigmented, radioresistant Deinococcus proteolyticus type strain (MRPT) - Alex Copeland (2018)
Deinococcus proteolyticus (ex Kobatake et al. 1973) Brook and Murray 1981 is one of currently 47 species in the genus Deinococcus within the family Deinococcaceae. Strain MRP T was isolated from feces of Lama glama and possesses extreme radiation resistance, a trait is shares with various other spe-cies of the genus Deinococcus, with D. proteolyticus being resistant up to 1.5 Mrad of gamma radia-tion. Strain MRP T is of further interest for its carotenoid pigment. The genome presented here is only the fifth completed genome sequence of a member of the genus Deinococcus (and the forth type strain) to be published, and will hopefully contribute to a better understanding of how members of this genus adaP T ed to high gamma- or UV ionizing-radiation. Here we describe the features of this organism, to-gether with the complete genome sequence and annotation. The 2,886,836 bp long genome with its four large plasmids of lengths 97 kbp, 132 kbp, 196 kbp and 315 kbp harbors 2,741 protein-coding and 58 RNA genes and is a part of the Genomic Encyclopedia of Bacteria and Archaea project.